HEART RHYTHM DISORDERS: ETIOLOGY, PATHOGENESIS, CLINICAL PRESENTATION, DIAGNOSIS, TREATMENT - Mamatov Yusufjon Sharipov Shaxbozbek Razzaqova Nozimaxon Shukurlayev Adhamjon (Journal of Science in Medicine and Life, 2024)
Heart rhythm disorders are one of the most common types of disorders, and their frequency cannot be accurately estimated [20]. Temporary rhythm disturbances occur in most healthy people. When diseases of internal organs occur, conditions are created for the development of heart rhythm disorders, which sometimes become the main manifestation of the clinical manifestation of the disease, for example, in thyrotoxicosis, coronary artery disease. Arrhythmias complicate the course of many cardiovascular diseases. The term "cardiac arrhythmia" refers to arrhythmias and heart blocks. Arrhythmia - disturbances in the frequency, regularity and consistency of heartbeats. Violation of the conduction of excitation causes the development of heart blocks.